Sustentación de caso: propuesta de un plan estratégico del ingreso al mercado peruano de una empresa del sector fast fashion - Sarmiento Fernandez, Ana Paula (2018)
The purpose of the present document is to analyze the business opportunity that entering to the Peruvian market means to the Fast Retailing group, and propose a strategic plan for it.